Electronic interaction and oxygen vacancy engineering of g-C3N4/α-Bi2O3 Z-scheme heterojunction for enhanced photocatalytic aerobic oxidative homo-/hetero-coupling of amines to imines in aqueous phase - Yanhua Gao; Tao Song; Xiuling Guo; Yan Zhang; Yong Yang (Green Carbon)
Photocatalytic oxidation coupling of amines represents a green and cost-effective method for the synthesis of highly value-added imines under visible light irradiation. However, the catalytic efficiency was severely limited by poor visible light response and easy recombination of photogenerated charge carriers. Herein, we report a g-C3N4/α-Bi2O3 Z-scheme heterojunction via electrostatic self-assembly of g-C3N4 nanosheets and oxygen-vacancy-rich α-Bi2O3 microsphere for visible-light driven oxidative coupling of amines to imines in H2O as green solvent at room temperature. Amines with diverse functional groups were efficiently converted into the corresponding imines in good to excellent yields. Impressively, this photocatalytic protocol is applicable for the challenging hetero-coupling of two structurally different amines to construct complicated asymmetric imines, which is the first report of photocatalytic hetero-coupling of amines to imines to our knowledge. Furthermore, the Z-scheme heterojunction also demonstrated high stability and could be readily separated and reused without obvious decay in activity and selectivity. Comprehensive characterizations and control experiments reveal the construction of Z-scheme heterojunction with intimate interface between g-C3N4 and α-Bi2O3 greatly boosts the transfer and separation of photogenerated charge carries and enhances the redox capability. Meanwhile, the surface oxygen vacancies in α-Bi2O3 also benefits the separation of photogenerated charge carriers and activation of reactants. These jointly contributed to an enhanced photocatalytic performance for oxidative coupling of amines to imines.